Analisis Yuridis Terhadap Pidana Pembayaran Uang Pengganti Pada Tindak Pidana Korupsi - Vially aviano; Lola Yustrisia (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Corruption is a crime that causes significant losses to individuals, society, and the state. To overcome these losses, a replacement money mechanism is arranged. This research aims to understand the legal basis and mechanism of implementing the crime of substitute money. The method used is normative juridical. The results of the study show that additional penalties in the form of compensation must be paid within one month after the verdict. Although a detailed explanation of the replacement money is not always available, this provision is regulated in Article 18 of the Law on the Eradication of Corruption and Article 10 of the Criminal Code.